Design and fabrication for next generation Magnetoencephalography - Hill, Ryan (2021)
Magnetoencephalography (MEG) is a functional neuroimaging technique which, via assessment of magnetic fields generated by neural current, probes human brain function with high spatial and temporal accuracy. Current state-of-the-art MEG systems use Superconducting QUantum Interference Devices (SQUIDs) to detect these magnetic fields, which are roughly a billion times smaller than the Earth’s magnetic field. However, these systems are expensive and rely on liquid helium to maintain superconductivity, which imposes significant limitations. The need for a thermally insulating vacuum between the participant’s head and the sensors means there is typically a 2-5 cm scalp-to-sensor distance. The sensors are also fixed in place in a one-size-fits-all helmet, and so the gap is inhomogeneous with the largest brain-to-sensor distances typically in frontal areas. This gap increases dramatically for individuals with small heads (e.g. infants). In addition, any movement greater than 5 mm relative to the static sensor array will significantly degrade data quality.